EULAR recommendations for the use of imaging of the joints in the clinical management of rheumatoid arthritis. Issue 6 (21st March 2013) - Colebatch, Alexandra N; Edwards, Christopher John; Østergaard, Mikkel; van der Heijde, Désirée; Balint, Peter V; D'Agostino, Maria-Antonietta; Forslind, Kristina; Grassi, Walter; Haavardsholm, Espen A; Haugeberg, Glenn; Jurik, Anne-Grethe; Landewé, Robert BM; et al.
Abstract : Objective: To develop evidence-based recommendations on the use of imaging of the joints in the clinical management of rheumatoid arthritis (RA). Methods: The task force comprised an expert group of rheumatologists, radiologists, methodologists and experienced rheumatology practitioners from 13 countries. Thirteen key questions on the role of imaging in RA were generated using a process of discussion and consensus. Imaging modalities included were conventional radiography, ultrasound, MRI, CT, dual-emission x-ray absorptiometry, digital x-ray radiogrammetry, scintigraphy and positron emission tomography. Research evidence was searched systematically for each question using MEDLINE, EMBASE and Cochrane CENTRAL. The experts used the evidence obtained from the relevant studies to develop a set of 10 recommendations. The strength of recommendation was assessed using a visual analogue scale. Results: A total of 6888 references was identified from the search process, from which 199 studies were included in the systematic review. Ten recommendations were produced encompassing the role of imaging in making a diagnosis of RA, detecting inflammation and damage, predicting outcome and response to treatment, monitoring disease activity, progression and remission. The strength of recommendation for each proposition varied according to both the research evidence and expert opinion. Conclusions: Ten key recommendations for the role of imaging in the management of RA were developed using research-based evidence and expert opinion.